Indan type low-dielectric-loss benzoxazine resin, resin composition for copper-clad plate as well as preparation method and application of indan type low-dielectric-loss benzoxazine resin

By combining indene-type low dielectric loss benzoxazine resin with phosphorus-containing epoxy resin and multifunctional epoxy resin to form a three-dimensional network cross-linked structure, the problem of insufficient dielectric and heat resistance of benzoxazine resin in copper clad laminates is solved, and the excellent performance of high frequency and high speed copper clad laminates is achieved.

CN119264355APending Publication Date: 2025-01-07SICHUAN DONGFANG INSULATING MATERIAL +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411318346.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing benzoxazine resins have shortcomings in heat resistance and dielectric properties, which limits their application in copper clad laminates.

Method used

A resin with multiple six-membered oxazine rings and indane rings was prepared by using indane-type low dielectric loss benzoxazine resin via the Mannich reaction. This resin was then combined with phosphorus-containing epoxy resin, multifunctional epoxy resin, and fillers to form a three-dimensional network cross-linked structure, which reduced the polar bond density and molecular polarizability, thereby improving dielectric properties and heat resistance.

Benefits of technology

The prepared copper-clad laminate has low dielectric loss, low dielectric constant, high heat resistance and good halogen-free flame retardant properties, making it suitable for the field of high-frequency and high-speed copper-clad laminates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005052860560000011
    Figure BDA0005052860560000011
  • Figure BDA0005052860560000021
    Figure BDA0005052860560000021
  • Figure BDA0005052860560000022
    Figure BDA0005052860560000022
Patent Text Reader

Abstract

The invention discloses indan type low-dielectric-loss benzoxazine resin, a resin composition for a copper-clad plate as well as a preparation method and application of the resin composition, and belongs to the technical field of electronic resin synthesis. The indan type low-dielectric-loss benzoxazine resin consists of two or more six-membered oxazine rings and a plurality of indan rings, and has the excellent characteristics of low dielectric loss, low dielectric constant, high heat resistance and the like; when the resin is prepared, the indan type amine resin, an aldehyde compound and a phenol compound are subjected to Mannich reaction; the resin composition for the copper-clad plate comprises low-dielectric-loss indan type benzoxazine resin, phosphorus-containing epoxy resin, multifunctional epoxy resin, an initiator, filler and a solvent, and is applied to preparation of the halogen-free flame-retardant low-dielectric-loss epoxy resin-based copper-clad plate. The prepared copper-clad plate has the excellent characteristics of low dielectric loss, low dielectric constant, high heat resistance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electronic resin synthesis, and in particular is an indane-type low-dissipation benzoxazine resin, a resin composition for copper-clad laminates, and a preparation method and application thereof. Background Art

[0002] In recent years, as electronic products have become shorter, thinner, more high-performance and more multifunctional, the number of electronic components has increased, the size has decreased, the weight has decreased and the integration has continued to increase. This has put forward higher requirements for the substrate materials used in printed circuit boards that carry electronic components to adapt to the development trend of increasingly high-frequency and high-speed electronic signal processing and signal transmission, and high-precision and high-integration electronic components. The requirements for substrate materials are specifically manifested in high heat resistance, excellent dielectric properties, low water absorption, and good processability.

[0003] Benzoxazine resin is a type of thermosetting resin formed by the Mannich reaction of phenol, amine and aldehyde. It undergoes ring-opening polymerization under heating or the action of a catalyst. During the curing process, no small molecules escape, the curing shrinkage is low, the pores are few, and it has good flame retardancy, thermomechanical properties, dielectric properties, etc. It can be widely used in the field of halogen-free flame-retardant copper clad laminates. However, in some fields with high requirements for heat resistance and dielectric properties, benzoxazine resin has the disadvantages of unsatisfactory heat resistance and dielectric properties, which limits its application in copper clad laminates. Summary of the invention

[0004] The object of the present invention is to provide an indane-type low dielectric loss benzoxazine resin, a resin composition for copper-clad laminates, and a preparation method and application thereof.

[0005] The purpose of the present invention is achieved through the following technical solutions:

[0006] An indane-type low dielectric loss benzoxazine resin is composed of two or more six-membered oxazine rings and multiple indane rings.

[0007] As some possible implementation methods of the present application, the general chemical structure formula of the low dielectric loss benzoxazine resin is shown in (I):

[0008]

[0009] In formula (I), n1 and n2 are integers of 0 to 32 and n1 and n2 are not 0 at the same time;

[0010] R1 and R2 are selected from hydrogen, an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, and an aryl group having 6 to 12 carbon atoms;

[0011] R3 is selected from an alkyl group having 1 to 8 carbon atoms or an aryl group having 6 to 10 carbon atoms;

[0012] R4 is selected from hydrogen, an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, an aryl group having 6 to 12 carbon atoms, or a group having the chemical structure shown in formula (II);

[0013]

[0014] In formula (II), X1 is selected from a chemical bond, an ether group, a sulfoxide group, an alkyl group having 1 to 8 carbon atoms, an aryl group having 6 to 11 carbon atoms, or a cycloalkyl group;

[0015] X2 is selected from an alkyl group having 1 to 8 carbon atoms or an aryl group having 6 to 10 carbon atoms;

[0016] X3 and X4 are selected from hydrogen, an alkyl group having 1 to 10 carbon atoms, and an aryl group having 6 to 10 carbon atoms.

[0017] As some possible implementation methods of the present application, the number average molecular weight of the low dielectric loss benzoxazine resin is 1000 to 10000.

[0018] In addition, to achieve the above-mentioned purpose, the present application also provides a method for preparing an indane-type low dielectric loss benzoxazine resin, wherein an indane-type amine resin is subjected to a Mannich reaction with an aldehyde compound and a phenol compound to obtain a low dielectric loss benzoxazine resin;

[0019] The indane-type amine resin has a general chemical structure as shown in formula (III):

[0020]

[0021] In formula (III), n3 and n4 are integers of 0 to 32 and n1 and n2 are not 0 at the same time;

[0022] R5 and R6 are selected from hydrogen, an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, and an aryl group having 6 to 12 carbon atoms.

[0023] As some possible implementation methods of the present application, the amino equivalent of the indane-type amine resin is 320 to 3380 g / mol.

[0024] As some possible implementation methods of the present application, the molar ratio of the indane-type amine resin amino group, the aldehyde compound aldehyde group, and the phenol compound hydroxyl group is 1:(2-2.1):(1-1.05).

[0025] As some possible implementation methods of the present application, the aldehyde compound is a compound containing an aldehyde group, including but not limited to formaldehyde, acetaldehyde, butyraldehyde, benzaldehyde, p-phenylformaldehyde, and o-methylbenzaldehyde.

[0026] As some possible embodiments of the present application, the phenolic compound includes monophenolic compounds and bisphenolic compounds, including but not limited to phenol, o-cresol, p-cresol, p-phenylphenol, p-octylphenol, 4-cyclohexylphenol, bisphenol A, bisphenol F, bisphenol S, bisphenol fluorene, tetramethyl bisphenol A, and 4,4'-dihydroxydiphenyl ether.

[0027] As some possible implementation methods of the present application, the low dielectric loss benzoxazine resin preparation process is carried out in a solvent, and the solvent is selected from toluene, xylene, cyclohexanone, cyclohexane, butanone, and methyl isobutyl ketone.

[0028] As some possible implementation methods of the present application, if the phenol compound is selected from bisphenol compounds, the low dielectric loss benzoxazine resin preparation process also includes a capping agent, which is a monoamine compound, including but not limited to aniline, p-methylaniline, p-phenylaniline, and 2,6-dimethylaniline; the amount of the capping agent added is 5% to 10% of the molar amount of the amino group of the indane-type ammonia resin.

[0029] As some possible implementation methods of the present application, in the preparation process of the low dielectric loss benzoxazine resin, the indane-type ammonia resin is first dissolved in a solvent, and then the aldehyde compound or aldehyde compound solution is added in batches or dropwise under alkaline conditions at room temperature, and then the phenol compound is added and the temperature is raised to react;

[0030] As some possible implementation methods of the present application, the preparation of low dielectric loss benzoxazine resin can be carried out under solvent reflux conditions, or under the catalysis of alkaline compounds and at 80 to 120° C.; wherein the alkaline compound is selected from any one of trimethylamine, triethylamine, sodium hydroxide, potassium hydroxide, potassium carbonate, sodium carbonate, sodium bicarbonate, and potassium bicarbonate.

[0031] As some possible implementation methods of the present application, during the preparation process of the low dielectric loss benzoxazine resin, solid alkaline compounds such as sodium hydroxide, potassium carbonate, etc. can be configured into a 20-40% by weight aqueous solution before being added; the amount of the alkaline compound is determined by the pH of the material, and generally the pH of the material needs to be adjusted to 9-12;

[0032] As some possible implementation methods of the present application, during the preparation process of the low dielectric loss benzoxazine resin, chromatography is used to detect the free end-capping agent or free phenol content (≤1 wt%) to determine the reaction endpoint.

[0033] In the present invention, in order to obtain a low dielectric loss indane benzoxazine resin with high purity, the low dielectric loss indane benzoxazine resin is synthesized under nitrogen conditions, and after the reaction is completed, a water washing step is required to remove the pH regulator in the material, and a distillation step is required to remove the solvent.

[0034] In addition, to achieve the above-mentioned purpose, the present application also provides a resin composition for copper clad laminates, comprising the following components in parts by weight:

[0035] 100 parts of low dielectric loss indane benzoxazine resin, 7-48 parts of phosphorus-containing epoxy resin, 2-15 parts of multifunctional epoxy resin, 0.01%-0.3% of the total mass of the resin initiator, 25%-53% of the total mass of the resin filler and 34%-36% of the total mass of the resin composition solvent; wherein the total mass of the resin is the total mass of the three resins: low dielectric loss indane benzoxazine resin, phosphorus-containing epoxy resin and multifunctional epoxy resin.

[0036] In this scheme, the resin composition for copper clad laminates contains a low dielectric loss indane benzoxazine resin, and non-polar rigid indane long chain segments can be introduced into the resin composition. Compared with resins such as bisphenol A benzoxazine resin, bisphenol F benzoxazine resin, and MDA benzoxazine resin, the low dielectric loss indane benzoxazine resin has a lower polar bond density and a main chain rigid structure, which reduces the polarizability of the molecular structure, thereby providing the resin composition with good dielectric properties; the phosphorus-containing epoxy resin in the resin composition can provide the resin composition with halogen-free flame retardant properties; the multifunctional epoxy resin can promote the formation of a three-dimensional network cross-linked structure, imparting good heat resistance and mechanical properties.

[0037] As some possible implementation methods of the present application, the phosphorus-containing epoxy resin is a DOPO-type epoxy resin, a DOPO-HQ-type epoxy resin, or a DOPO-NQ-type epoxy resin having a phosphorus content of 2% to 3.2% by mass. The DOPO is the abbreviation of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, the DOPO-HQ is the abbreviation of 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide, and the DOPO-NQ is the abbreviation of 10-(2,7-dihydroxynaphthyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene-10-oxide;

[0038] As some possible implementation methods of the present application, the multifunctional epoxy resin is a resin compound containing three or more epoxy groups, including but not limited to phenol-type novolac epoxy resin, dicyclopentadiene phenol-type epoxy resin, bisphenol A-type novolac epoxy resin, biphenyl phenol-type epoxy resin, o-cresol novolac epoxy resin, aralkylphenol epoxy resin, phenol benzaldehyde epoxy resin, and tetraphenol ethane epoxy resin.

[0039] As some embodiments of the present application, the initiator includes but is not limited to imidazoles such as 4-dimethylaminopyridine, 2-methylimidazole, 1-benzyl-2-methylimidazole, 2-ethyl-4-methylimidazole, 2-ethylimidazole and 2-ethyl-4-methylimidazole; tertiary amines such as 2-(dimethylaminomethyl)phenol; phosphines such as triphenylphosphine;

[0040] As some possible implementation methods of the present application, the filler includes but is not limited to silicon dioxide, montmorillonite, magnesium oxide, aluminum oxide, mica powder, barium sulfate, kaolin, silicon nitride, boron nitride, zirconium oxide, aluminum nitride, graphite, titanium dioxide, talc, and iron oxide;

[0041] As some possible implementation methods of the present application, the solvent A includes but is not limited to acetone, butanone, cyclohexanone, methyl isobutyl ketone, toluene, propylene glycol monomethyl ether, and propylene glycol methyl ether acetate.

[0042] In addition, to achieve the above-mentioned purpose, the present application also provides an application of a resin composition for copper clad laminates in the preparation of halogen-free flame retardant low dielectric loss epoxy resin-based copper clad laminates. Specifically, the preparation method of the halogen-free flame retardant low dielectric loss epoxy resin-based copper clad laminates comprises the following steps:

[0043] S1. The copper-clad laminate is uniformly mixed with a resin composition to form a resin adhesive, the glass fiber is arranged in the resin adhesive and then taken out after being immersed, most of the solvent is removed by hanging at room temperature, and then placed in an oven for baking to obtain a halogen-free flame retardant low dielectric loss semi-cured sheet;

[0044] S2. Stack several layers of halogen-free flame-retardant low dielectric loss semi-cured sheets, attach copper foil on both sides, place them in a vacuum hot press for pressing, release the pressure after pressing and cool naturally to obtain a halogen-free flame-retardant low dielectric loss epoxy resin-based copper clad laminate.

[0045] Wherein, in step S1, the baking temperature is 130° C. to 170° C., and the baking time is 1 to 10 minutes.

[0046] In step S2, the specific steps of pressing are: first, the temperature is raised from room temperature to 170°C at a rate of 3°C / min, the pressure is raised from 0.5MPa to 4MPa at a rate of 0.1MPa / 1min, the vacuum is evacuated to less than 50torr, and pressing is maintained for 1 to 2h; then the temperature is raised to 200 to 240°C and the constant pressure is maintained for 3 to 5h.

[0047] As some possible implementation modes of the present application, the glass fiber cloth model is selected from 1080E, 2116, 2313, 3313, and 7628.

[0048] There is no limitation on the number of laminated layers of the semi-cured sheets, which can be selected from any number within the process achievable range.

[0049] Compared with the prior art, the present invention has the following beneficial effects:

[0050] 1. The indane-type low dielectric loss benzoxazine resin provided in the present application is a multifunctional benzoxazine resin that can form a three-dimensional network cross-linked structure. The indane ring main chain it contains has a large long chain rigidity and low polarity, and has excellent properties such as low dielectric loss, low dielectric constant, and high heat resistance. It can be used in the field of high-frequency and high-speed copper clad laminates.

[0051] 2. In the resin composition for copper clad laminates provided in the present application, the low dielectric loss indane-type benzoxazine resin can introduce non-polar rigid long chain segments into the resin composition, which can reduce the polar bond density, thereby reducing the polarizability of the molecular structure, so that the resin composition has good dielectric properties and the indane rigid structure imparts good heat resistance; the phosphorus-containing epoxy resin as a reactive flame retardant can provide the resin composition with good halogen-free flame retardant properties; the multifunctional epoxy resin can enable the resin composition to maintain an appropriately high level of crosslinking, and further impart good heat resistance and mechanical properties to the resin composition.

[0052] 3. The copper-clad laminate prepared by using the resin composition for copper-clad laminates of the present application has the performance characteristics of the resin composition for copper-clad laminates of the present application, and the obtained copper-clad laminate has excellent comprehensive performance: dielectric constant of 3.23-3.35 and dielectric loss of 0.004-0.0051 at 10GHz; glass transition temperature of 188-197°C, good toughness of the board, and flame retardancy reaching V0 level.

[0053] 4. The preparation process of the present invention is easy to operate, and the prepared indane-type low dielectric loss benzoxazine resin and resin composition for copper-clad laminate are suitable for the field of high-performance printed circuit boards and have strong practicality. DETAILED DESCRIPTION

[0054] Part 1 Preparation of Indane-type Low Dielectric Loss Benzoxazine Resin (Example 1-1 to Example 1-5)

[0055] Example 1-1

[0056] In a four-necked reaction bottle equipped with a mechanical stirrer, a thermometer, nitrogen, and a reflux condenser, 100 parts by mass of an indane-type amine resin (the chemical structure formula is the same as that of Formula III, R5 and R6 are hydrogen atoms, and the amino equivalent is 438 g / mol) and 350 parts by mass of toluene are added in sequence and stirred to dissolve at room temperature, and then 6 parts by mass of triethylamine are added. After sufficient stirring, an aqueous formaldehyde solution (14 parts by mass of formaldehyde) is added dropwise, and the material temperature is controlled not to exceed 30°C. After the dropwise addition is completed, the temperature is maintained and stirred for 1 hour, 22 parts by mass of phenol is added, and the temperature is raised and refluxed for reaction. When the free phenol detected by chromatography is ≤1%, the reaction is terminated. After washing with water and desolvation under reduced pressure, the indane-type low dielectric loss benzoxazine resin of Example 1-1 can be obtained. The number average molecular weight detected by gel chromatography is 1759. The obtained indane-type low dielectric loss benzoxazine resin is heated and cured to obtain a casting body. The casting body has a glass transition temperature of 221°C, a dielectric constant of 2.08, and a dielectric loss of 0.0031.

[0057] Example 1-2

[0058] On the basis of the method and process of Example 1-1, the formaldehyde aqueous solution product (14 parts by mass of formaldehyde) is replaced with a benzaldehyde toluene solution (24.8 parts by mass of phenol benzaldehyde, accounting for 30% by mass), and other conditions remain unchanged, to obtain the indane-type low dielectric loss benzoxazine resin of Example 1-2. The number average molecular weight detected by gel chromatography is 1802. The obtained indane-type low dielectric loss benzoxazine resin is heated and cured to obtain a casting. The casting has a glass transition temperature of 219°C, a dielectric constant of 2.04, and a dielectric loss of 0.0029.

[0059] Examples 1-3

[0060] Based on the method and process of Example 1-2, 100 parts by mass of indane-type amine resin (the general chemical structure formula is the same as Formula III, R5 and R6 are hydrogen atoms, and the amino equivalent is 438 g / mol) are replaced with 198 parts by mass of indane-type amine resin (the general chemical structure formula is the same as Formula III, R5 and R6 are hydrogen atoms, and the amino equivalent is 869 g / mol), and other conditions remain unchanged. The indane-type low dielectric loss benzoxazine resin of Example 1-3 can be obtained. The number average molecular weight is 3101 as detected by gel chromatography. The obtained indane-type low dielectric loss benzoxazine resin is heated and cured to obtain a casting. The casting has a glass transition temperature of 216°C, a dielectric constant of 2.03, and a dielectric loss of 0.0025.

[0061] Examples 1-4

[0062] Based on the method and process of Examples 1-2, 100 parts by mass of indane-type amine resin (the general chemical structure is the same as Formula III, R5 and R6 are hydrogen atoms, and the amino equivalent is 438 g / mol) are replaced with 211 parts by mass of indane-type amine resin (the general chemical structure is the same as Formula III, R5 and R6 are methyl groups, and the amino equivalent is 930 g / mol), and other conditions remain unchanged. The indane-type low dielectric loss benzoxazine resin of Examples 1-4 can be obtained, and the number average molecular weight detected by gel chromatography is 2932. The obtained indane-type low dielectric loss benzoxazine resin is heated and cured to obtain a casting, and the casting has a glass transition temperature of 217°C, a dielectric constant of 2.01, and a dielectric loss of 0.0023.

[0063] Examples 1-5

[0064] Based on the method and process of Example 1-4, 22 parts by mass of phenol are replaced by 46.9 parts by mass of bisphenol F, 1.1 parts by mass of aniline are added after heating and reflux for 5 hours, and the temperature is continued to rise and reflux until the free aniline is ≤1%. Other conditions remain unchanged, and the indane-type low dielectric loss benzoxazine resin of Example 1-5 can be obtained. The number average molecular weight detected by gel chromatography is 3533, the glass transition temperature of the cast body is 232°C, the dielectric constant is 2.02, and the dielectric loss is 0.0021.

[0065] Part 2 Preparation of Halogen-free Flame-retardant Resin Copper Clad Laminate (Examples 2-1 to 2-5)

[0066] S1: 100 parts by mass of low dielectric loss indane benzoxazine resin, 34-48 parts by mass of phosphorus-containing epoxy resin, 24-50 parts by mass of multifunctional epoxy resin, 0.01%-0.3% of the total mass of the resin initiator, 25%-53% of the total mass of the resin filler and 34%-36% of the total mass of the resin composition solvent are prepared into a resin glue, and then the glass fiber is arranged in the resin glue, immersed and taken out, and most of the solvent is removed by hanging at room temperature, and then placed in an oven at a temperature of 130°C-170°C for 1-10 minutes to obtain a halogen-free flame retardant low dielectric loss semi-cured sheet of the embodiment;

[0067] S2: Stack several layers of semi-cured sheets, attach copper foil on both sides, place them in a vacuum hot press, raise the temperature from room temperature to 170°C at a heating rate of 3°C / min, increase the pressure from 0.5MPa to 4MPa at a rate of 0.1MPa / 1min, evacuate to less than 50torr, keep pressing for 1 to 2h, then raise the temperature to 200 to 240°C and maintain constant pressure for 3 to 5h, release the pressure and cool naturally, to obtain the halogen-free flame retardant and low dielectric loss epoxy resin based copper clad laminates of Examples 2-1 to 2-5.

[0068] Comparative Example 1

[0069] 100 parts by mass of bisphenol F benzoxazine resin (DFE128), 45 parts by mass of phosphorus-containing epoxy resin (DFE202), 38 parts by mass of bisphenol A novolac epoxy resin, 0.51 parts by mass of 2-methylimidazole, 63 parts by mass of silicon dioxide, and 133 parts by mass of butanone are prepared into a resin glue solution with a mass percentage content of 65%±1%, and then a glass fiber cloth is impregnated, and then the glass fiber cloth impregnated with the resin glue solution is baked at a temperature of 130°C to 170°C for 1 to 10 minutes to obtain a low-loss prepreg;

[0070] Stack 6 low-loss semi-cured sheets and attach copper foil on both sides, place them in a vacuum hot press, raise the temperature from room temperature to 175°C at a heating rate of 3°C / min, increase the pressure from 0.5MPa to 4MPa at a rate of 0.1MPa / 1min, evacuate to less than 50torr, keep pressing for 1-2h, then raise the temperature to 200-240°C and keep constant pressure for 3-5h, release the pressure and cool naturally to obtain the copper clad laminate of comparative example 1.

[0071] Comparative Example 2

[0072] 100 parts by mass of the indane-type low dielectric loss benzoxazine resin prepared in Example 1-5, 35 parts by mass of biphenyl epoxy resin DFE260H, 0.45 parts by mass of 2-ethyl-4-methylimidazole, 49 parts by mass of silicon dioxide, and 100 parts by mass of butanone are prepared into a resin glue having a mass percentage content of 65%±1%, and then the glass fiber cloth is impregnated, and then the glass fiber cloth impregnated with the resin glue is baked at a temperature of 130°C to 170°C for 1 to 10 minutes to obtain a low-loss prepreg;

[0073] Stack 8 low-loss semi-cured sheets and attach copper foil on both sides, place them in a vacuum hot press, raise the temperature from room temperature to 175°C at a heating rate of 3°C / min, increase the pressure from 0.5MPa to 4MPa at a rate of 0.1MPa / 1min, evacuate to less than 50torr, keep pressing for 1-2h, then raise the temperature to 200-240°C and keep constant pressure for 3-5h, release the pressure and cool naturally to obtain the copper clad laminate of comparative example 2.

[0074] Table 1 is a table of raw material components, dosages and performance parameters of copper clad laminates in Examples 2-1 to 2-5 and Comparative Examples 1 and 2, and the units of component dosages in the table are parts by mass.

[0075] The English letters in Table 1 refer to the following:

[0076] A1: indane-type low dielectric loss benzoxazine resin prepared in Example 1-1;

[0077] A2: Indane-type low dielectric loss benzoxazine resin prepared in Example 1-2;

[0078] A3: Indane-type low dielectric loss benzoxazine resin prepared in Example 1-3;

[0079] A4: Indane-type low dielectric loss benzoxazine resin prepared in Example 1-4;

[0080] A5: Indane-type low dielectric loss benzoxazine resin prepared in Example 1-5;

[0081] B: DOPO type phosphorus-containing epoxy resin DFE202;

[0082] C1: Bisphenol A novolac epoxy resin EMTE200;

[0083] C2: biphenyl phenol type epoxy resin DFE260H;

[0084] D: 2-ethyl-4-methylimidazole;

[0085] E: Silica DQ1040;

[0086] F is: butanone.

[0087] In addition, the relevant standards adopted by the technical indicators in Table 1 are as follows:

[0088] Glass transition temperature Tg: measured by dynamic mechanical analysis (DMA) according to the DMA method specified in 2.4.24.4 of IPC-TM-650;

[0089] Dielectric constant Dk and dielectric loss Df: Use SPDR method to test 10GHz data according to the method specified in IEC 61189-2-721;

[0090] Thermal delamination time T300: measured according to the method specified in 2.4.24.1 of IPC-TM-650;

[0091] Plate toughness: Use a drop hammer impact tester with a drop hammer height of 40cm and a drop hammer mass of 1kg. To evaluate toughness, the clearer, more slender and smaller the cross at the impact point is, the better the toughness of the product is, indicated by ◎; the more blurred the cross is, the larger the area is, the worse the toughness is, the greater the brittleness is, indicated by △; if the cross is between clear and blurred, the toughness of the product is average, indicated by ○;

[0092] Solder immersion resistance time with copper foil: Take a plate sample with a size of 100mm×100mm and copper foil on both sides, immerse it in 288℃ solder respectively, and take the average time without delamination and explosion;

[0093] UL 94 flame retardant performance test: measured according to UL94 vertical burning test method.

[0094] Table 1:

[0095]

[0096]

[0097] It can be seen from Table 1 that the copper clad laminate prepared by using the indane-type low-loss benzoxazine resin and the resin composition for copper clad laminate of the present application has good dielectric properties, heat resistance, flame retardancy and toughness.

[0098] Compared with Examples 2-1 to 2-5, the toughness and dielectric properties of the copper clad laminate prepared by using bisphenol F type benzoxazine resin, phosphorus-containing epoxy resin, bisphenol A novolac epoxy resin and other components in Comparative Example 1 are poor. It can be seen from Comparative Example 2 that the indane type low-loss benzoxazine resin has certain flame retardant properties, but there are deficiencies, and other flame retardants such as phosphorus-containing epoxy resin need to be added for synergistic flame retardancy, so as to achieve halogen-free flame retardancy of the copper clad laminate.

[0099] The technical contents not specifically described in the present invention and the above embodiments are the same as the prior art, and the raw materials are all commercially available products.

Claims

1. An indane-type low dielectric loss benzoxazine resin, characterized in that: It is composed of two or more six-membered oxazine rings and multiple indane rings.

2. The indane-based low dielectric loss benzoxazine resin according to claim 1, characterized in that: The general chemical structure formula of the low dielectric loss benzoxazine resin is shown in (I): In formula (I), n1 and n2 are integers of 0 to 32 and n1 and n2 are not 0 at the same time; R1 and R2 are selected from hydrogen, an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, and an aryl group having 6 to 12 carbon atoms; R3 is selected from an alkyl group having 1 to 8 carbon atoms or an aryl group having 6 to 10 carbon atoms; R4 is selected from hydrogen, an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, an aryl group having 6 to 12 carbon atoms, or a group having the chemical structure shown in formula (II); In formula (II), X1 is selected from a chemical bond, an ether group, a sulfoxide group, an alkyl group having 1 to 8 carbon atoms, an aryl group having 6 to 11 carbon atoms, or a cycloalkyl group; X2 is selected from an alkyl group having 1 to 8 carbon atoms or an aryl group having 6 to 10 carbon atoms; X3 and X4 are selected from hydrogen, an alkyl group having 1 to 10 carbon atoms, and an aryl group having 6 to 10 carbon atoms.

3. The indane-based low dielectric loss benzoxazine resin according to claim 1, characterized in that: The low dielectric loss benzoxazine resin has a number average molecular weight of 1,000 to 10,000.

4. The method for preparing an indane-based low dielectric loss benzoxazine resin according to any one of claims 1 to 3, characterized in that: The indane amine resin is subjected to a Mannich reaction with an aldehyde compound and a phenol compound to obtain a low dielectric loss benzoxazine resin; The indane-type amine resin has a general chemical structure as shown in formula (III): In formula (III), n3 and n4 are integers of 0 to 32 and n1 and n2 are not 0 at the same time; R5 and R6 are selected from hydrogen, an alkyl group having 1 to 10 carbon atoms, an alkoxy group having 1 to 10 carbon atoms, and an aryl group having 6 to 12 carbon atoms.

5. The method for preparing an indane-based low dielectric loss benzoxazine resin according to claim 4, characterized in that: The amino equivalent of the indane-type amine resin is 320 to 3380 g / mol.

6. The method for preparing an indane-based low dielectric loss benzoxazine resin according to claim 4, characterized in that: The molar ratio of the indane-type amine resin amino group, the aldehyde compound aldehyde group, and the phenol compound hydroxyl group is 1:(2-2.1):(1-1.05).

7. A resin composition for copper-clad laminates, characterized in that: It includes the following components by weight: 100 parts of the low dielectric loss indane-type benzoxazine resin according to any one of claims 1 to 3, 7 to 48 parts of a phosphorus-containing epoxy resin, 2 to 15 parts of a multifunctional epoxy resin, 0.01% to 0.3% of the total mass of the resin by weight of an initiator, 25% to 53% of the total mass of the resin by weight of a filler, and 34% to 36% of the total mass of the resin composition by weight of a solvent; wherein the total mass of the resin is the total mass of the three resins of the low dielectric loss indane-type benzoxazine resin, the phosphorus-containing epoxy resin, and the multifunctional epoxy resin.

8. A resin composition for copper-clad laminates according to claim 7, characterized in that: The phosphorus-containing epoxy resin is a DOPO type epoxy resin, a DOPO-HQ type epoxy resin, or a DOPO-NQ type epoxy resin, wherein the phosphorus content by mass is 2% to 3.2%.

9. A resin composition for copper-clad laminates according to claim 7, characterized in that: The multifunctional epoxy resin is a resin compound containing three or more epoxy groups, including but not limited to phenol-type novolac epoxy resin, dicyclopentadiene phenol-type epoxy resin, bisphenol A novolac epoxy resin, biphenyl phenol-type epoxy resin, o-cresol novolac epoxy resin, aralkylphenol epoxy resin, phenol benzaldehyde epoxy resin, and tetraphenol ethane epoxy resin.

10. Use of a resin composition for copper clad laminate according to any one of claims 7 to 9 in preparing halogen-free flame retardant low dielectric loss epoxy resin-based copper clad laminates, characterized in that: The preparation method of the halogen-free flame-retardant low dielectric loss epoxy resin-based copper clad laminate comprises the following steps: S1. The copper-clad laminate is uniformly mixed with a resin composition to form a resin adhesive, the glass fiber is arranged in the resin adhesive and then taken out after being immersed, most of the solvent is removed by hanging at room temperature, and then placed in an oven for baking to obtain a halogen-free flame retardant low dielectric loss semi-cured sheet; S2. Stack several layers of halogen-free flame-retardant low dielectric loss semi-cured sheets, attach copper foil on both sides, place them in a vacuum hot press for pressing, release the pressure after pressing and cool naturally to obtain a halogen-free flame-retardant low dielectric loss epoxy resin-based copper clad laminate.